Incidence of chest X‐ray abnormalities early in the third trimester of twin pregnancy and its relationship with the subsequent development of preeclampsia. Issue 1 (17th November 2021) - Yagi, Kazunobu; Kawaguchi, Haruna; Yamamoto, Ryo; Hayashi, Shusaku; Ishii, Keisuke
Abstract: Aim: To clarify the incidence of abnormal findings on chest X‐ray (CXR) early in the third trimester of twin pregnancy and its relationship with the development of preeclampsia and preeclampsia‐related diseases. Methods: This was a retrospective cohort study conducted among women with twin pregnancies who underwent chest radiography for preoperative screening early in the third trimester and delivered at our center at >34 weeks' gestation from 2013 to 2017. The primary outcome was the incidence of positive CXR findings, defined either as cardiomegaly or blunting of the costophrenic angle. The secondary outcome was the incidence of maternal complications, including preeclampsia; hemolytic, elevated liver enzymes, and low platelet syndrome; eclampsia; cerebrovascular disease; and placental abruption. We evaluated the significance of positive CXR findings, in addition to confounding factors, in the subsequent development of preeclampsia. Results: During the study period, 358 twin pregnancies were identified, and 330 were finally enrolled. The incidence of positive CXR findings was 18.2%. The incidence of preeclampsia in the CXR‐positive group was 36.7% (22/60), which was significantly higher than that in the CXR‐negative group (7.0% [19/270]) ( p  < 0.01). Moreover, positive CXR findings were independently associated with subsequent preeclampsia (adjusted odds ratio: 9.15, 95% confidence interval: 4.13–20.3). Conclusion: In twin pregnancies, the incidence of CXR abnormalities early in the third trimester was 18.2%, even without the development of hypertension. This should be considered a significant risk factor for subsequent preeclampsia.